Perspectives on Practical Pedagogy for Teachers in Islamic Boarding Schools - Ummah Karimah; Wiwied Widiyanti; Hendriadi Hendriadi; Sadari Sadari (STAI Hubbulwathan Duri, 2023)
Islamic boarding schools are genuine educational institutions where students are taught about character education through Islamic boarding schools. This research aims to take a closer look at the pedagogic practice of teachers who lead us to reflect on the function of genuine national education in Islamic boarding schools. The method used is qualitative by collecting data through interviews and observation of teachers who teach at schools located in Islamic boarding schools with the aim of obtaining development and new knowledge. The results of this study suggest that Islamic boarding schools in society are not only for fulfilling group interests. Community groups constitute the majority of the Indonesian nation and are multicultural and have cultural wealth, and in the future, as the main social capital and cultural capital in dealing with various global societal problems in the development of a glorious Indonesia through practical education for Islamic boarding school teachers as applied in education in Islamic boarding schools.